2017
DOI: 10.1037/neu0000370
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated hemispheric asymmetry in metaphor processing among adults with ADHD.

Abstract: Our results suggest that the hemispheric processing of adults with ADHD is less lateralized than the hemispheric processing of control participants. Moreover, the diminished lateralization of metaphor processing along with deficient sustained attention may reflect distinct cognitive mechanisms underlying ADHD and as such our results support multiple pathway models of ADHD. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
(121 reference statements)
1
4
0
1
Order By: Relevance
“…Thus, it is not surprising that bilinguals as well as monolinguals showed a left hemisphere advantage for familiar metaphor processing. These results support previous reports of a LH advantage in monolinguals (Faust & Mashal, 2007; Segal et al, 2017) and in bilinguals when tested in their dominant (Faust, Ben-Artzi, & Vardi, 2012; Mashal et al, 2015) and non-dominant languages (Briellmann et al, 2004; Hull & Vaid, 2007; Vingerhoets et al, 2003). In other words, although bilinguals scored lower than monolinguals in all English proficiency tests, and they recognized fewer metaphors, they still appeared to access metaphors in the left-hemisphere automatically via a search for “stored lexical units” (activated in the LH) rather than by looking for distant semantic associations (activated in the RH).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, it is not surprising that bilinguals as well as monolinguals showed a left hemisphere advantage for familiar metaphor processing. These results support previous reports of a LH advantage in monolinguals (Faust & Mashal, 2007; Segal et al, 2017) and in bilinguals when tested in their dominant (Faust, Ben-Artzi, & Vardi, 2012; Mashal et al, 2015) and non-dominant languages (Briellmann et al, 2004; Hull & Vaid, 2007; Vingerhoets et al, 2003). In other words, although bilinguals scored lower than monolinguals in all English proficiency tests, and they recognized fewer metaphors, they still appeared to access metaphors in the left-hemisphere automatically via a search for “stored lexical units” (activated in the LH) rather than by looking for distant semantic associations (activated in the RH).…”
Section: Discussionsupporting
confidence: 91%
“…The question is does that also apply to metaphor processing? 1 One way to address this question is to examine the hemispheric processing of metaphors, since familiar (conventional) metaphors were processed differently from nonfamiliar (novel) metaphors by the left versus the right hemispheres in monolinguals. Several studies have suggested that familiar metaphors are lexicalized, and therefore are processed more efficiently in the left hemisphere (LH; Faust & Mashal, 2007; Segal, Shalev, & Mashal, 2017), which focuses on a single dominant interpretation (fine semantic coding) and closely related semantic associations (Beeman, 1998; Jung-Beeman, 2005). In contrast, novel and unfamiliar metaphors are processed more efficiently in the right hemisphere (RH), which loosely activates and maintains large semantic fields of distant associates (coarse semantic coding).…”
mentioning
confidence: 99%
“…Participants were instructed to respond to a target-stimulus (circle or triangle), appearing inside a cued (a light flashing briefly) or an un-cued rectangle, located to the right or left of a fixation point. The performance ratio of response time to invalid-cue trials (the target is not on the cued rectangle), vs. valid-cue trials serves as an index of the ability to orient to stimulus location [23,53].…”
Section: Methodsmentioning
confidence: 99%
“…To eliminate trials with exceptionally long latencies in the selective-, orienting- and executive-attention tasks, we calculated mean RTs for correct responses for each condition, after excluding trials in which RT exceeded 4000 ms, and trials in which RT deviated more than 2 standard deviations from the participant's mean RT. In accordance with previous studies [52,53], we extracted for the selective-, orienting- and executive-attention tasks a single summarizing measure—inverse efficiency index [IEI]. As the IEI included a skewed RTs distribution, it was transformed to a natural log, reflecting the performance efficiency of the corresponding attention function.…”
Section: Methodsmentioning
confidence: 99%
“…Abnormalities in cerebral lateralization and hemispheric asymmetries have been reported in ADHD (Doi & Shinohara, 2017;Douglas et al, 2018;Li et al, 2019;Segal et al, 2017) and ASD (Carper et al, al., 2016;Doi & Shinohara, 2017;Fu et al, 2020;Wei et al, 2018) and can be explained in particular by asymmetrical distributions in neurotransmission linked to the cholinergic, dopaminergic, serotonergic and noradrenergic systems (Klimkeit and Bradshaw, 2006). Kaufman et al (2010) suggested that creative cognition could lie in hemispheric asymmetry and the meta-analysis of Mihov et al (2010) highlighted the lateralization during creative thinking.…”
Section: A) Lateralization Of Brain Functions and Cerebral Asymmetriesmentioning
confidence: 99%